Effect Of Spiritual Assistance On The Level Of Anxiety In Parents With Children With Attention Deficit Hyperactvity Disorder (ADHD) - yati, indri (Sahabat Publikasi Kuu, 2023)
Children with ADHD are a condition of children with various developmental problems such as impaired motor, sensory, language and psychomotor development, this condition can affect a variety of lives. The purpose of this study was to find out how the anxiety level of parents with children with ADHD before and after being given spiritual assistance. This research is a study with a pre-experimental design because there are no control variables and the sample is not chosen randomly. The design used is the one-group pretest-posttest design, so that it can be compared before and after treatment. This research was conducted in the working area of ​​the Colomadu Health Center on March 20-31, 2023. The total population in this study were 24 respondents, and the number of samples was also 24 respondents. Analysis it is found that the p value = 0.000 and the mean is 4.761. this means that the mean value is positive and indicates that there is a decrease in anxiety before and after the treatment of providing spiritual assistance to parents with children with ADHD. This study shows that there is an influence between giving spiritual assistance interventions in the form of prayer guidance and tawakkal on the anxiety level of parents with children with ADHD. This shows that the anxiety of parents with children with ADHD can be overcome by surrendering and drawing closer to God Almighty to pray for the healing of their children. and this means that the readiness of parents can also affect the child's recovery.